2017
DOI: 10.1111/jam.13559
|View full text |Cite
|
Sign up to set email alerts
|

Production of bioethanol in sugarcane bagasse hemicellulosic hydrolysate byScheffersomyces parashehatae,Scheffersomyces illinoinensisandSpathaspora arborariaeisolated from Brazilian ecosystems

Abstract: This study widens the scope for future researches that may examine the native yeasts presented, as limited studies have investigated these species previously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…Cellulose nanofiber is embedded in a complex network of hemicellulose and lignin, which is compared to the structure of reinforced concrete [11]. Many researchers have devoted their efforts to isolating cellulose, lignin and hemicellulose from such a complex structure for bio-based materials [12,13,14]. However, the separation of SCB fractions usually involves complex procedures associated with high energy input, hazardous chemicals and high cost [15].…”
Section: Introductionmentioning
confidence: 99%
“…Cellulose nanofiber is embedded in a complex network of hemicellulose and lignin, which is compared to the structure of reinforced concrete [11]. Many researchers have devoted their efforts to isolating cellulose, lignin and hemicellulose from such a complex structure for bio-based materials [12,13,14]. However, the separation of SCB fractions usually involves complex procedures associated with high energy input, hazardous chemicals and high cost [15].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, despite extensive research in this field, the majority of the studies concerning xylose (as the most relevant pentose) conversion to ethanol have been performed with only these few yeast species. This trend has recently changed after studies describing the isolation, description and application of new xylose-fermenting yeasts from particular habitats, such as wood-boring insects and rotting wood [185]. These new species belong to the xylose-fermenting clades Spathaspora and Scheffersomyces [186].…”
Section: Chemicals From Hemicellulosementioning
confidence: 99%
“…Methods for the isolation of yeast strains have been reported previously by Cadete et al 25 . The yeast strains were isolated from tree bark, decaying wood, sugarcane filter cake, insect frass, water, and cactus samples 24,30,32,33 . These isolates were stored in the Collection of Microorganisms and Cells of the Federal University of Minas Gerais (a public microbial collection) at −80 °C.…”
Section: Methodsmentioning
confidence: 99%
“…reported that Wickerhamomyces rabaulensis is a xylitol‐producing yeast (0.36 g g −1 ) that utilizes xylose (10 g L −1 ) as the carbon source. During studies on yeasts associated with the rotting wood in Brazil's forest ecosystems, we isolated several novel strains of C. xylosilytica and W. rabaulensis 24,30,32,33 . Until now, these strains have not been assessed for their potential to produce xylitol.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation